Perceptions of Students Academy of Language Studies on Malay Language Learning in New Media - Elias, Muhammad Isa bin; Samsudin, Nurul Haniza; Bukhari, Nur Azimah Mohd; Mansur, Akhmad; Omar, Mardian Shah; Drani, Shaza Shahira (International Journal of Language Pedagogy, 2023)
The development of information and communication technology has typically made it easier for information that b received quickly through the uses of devices such as laptops or smartphones that have internet access. New media is gaining more attention in society as many parties have opened their eyes to the importance of new media. New media is not only an alternative field of communication, but also of interest to other fields such as education field. New media also serves as a platform that imparts learning knowledge. TikTok and Instagram have become mediums for users to upload learning videos for their followers. This study was conducted to identify and analyze the perceptions of Academy of Language Studies, UiTM students on Malay language learning in new media. This study focuses on students of LG241, which is the Malay Language Professional Communication program. This study used a questionnaire form instrument distributed to 30 students consisting of 17 female students and 13 male students. This study uses the Technology Acceptance Model (TAM) theory by Davis (1989). This theory emphasizes four factors, namely usability factor, usefulness factor, personal and social network, and relevance. The results of the study found that most students can accept the learning of Malay language in new the media.